Case Report: Two cases of advanced primary cardiac angiosarcoma treated with anlotinib and a retrospective analysis of the literature - Yang, Pan; Xiong, Fu; Zhu, Bingjing; Gong, Liang; Tang, Chunlan (Frontiers in Cardiovascular Medicine, 2024)
Primary cardiac angiosarcoma is a rare malignant soft-tissue sarcoma derived from vascular endothelial cells or lymphatic endothelial cells, with a high malignancy, poor prognosis, and a lack of effective medical therapy. This article reports on two patients with primary cardiac angiosarcoma who received first-line treatment with multi-targeted anti-angiogenic agent, anlotinib monotherapy. The treatment rapidly controlled pleural and pericardial effusion, significantly reduced the tumor, improved symptoms, and showed satisfactory recent efficacy. This indicates that anlotinib offers a new first-line treatment option for advanced primary cardiac angiosarcoma.